Circulating microRNAs as biomarkers for hepatocellular carcinoma - Qu, Kevin Z; Zhang, Ke; Li, HaiRong; Afdhal, Nezam H; Albitar, Maher (Journal of clinical gastroenterology, 2011)
We investigated whether measurement of serum levels of the microRNAs (miRNAs) miR-16, miR-195, and miR-199a, alone or in combination with conventional serum markers, can help to differentiate hepatocellular carcinoma (HCC) from chronic liver diseases (CLDs). Recent reports suggest a link between aberrant expression of miRNA, and HCC. This retrospective analysis was conducted using sera from 105 HCC patients, 107 CLD patients, and 71 normal control subjects. The miRNAs were measured using real-time reverse transcription-polymerase chain reaction. The conventional HCC markers α-fetoprotein (AFP), lens culinaris agglutinin-reactive AFP (AFP-L3%), and des-γ-carboxyprothrombin (DCP) were measured with commercial kits. Serum levels of miR-16 and miR-199a were significantly lower in HCC than in CLD patients or control subjects (P<0.01). As a single marker, miR-16 had the highest sensitivity for HCC, followed by miR-199a, AFP, DCP, AFP-L3%, and miR-195. The combination of miR-16, AFP, AFP-L3%, and DCP yielded the optimal combination of sensitivity (92.4%) and specificity (78.5%) for HCC, overall and when analysis was restricted to patients with tumors size smaller than 3 cm. As a second-line HCC marker, miR-16 yielded positive HCC predictions in 18 of the 26 (69.2%) HCC patients with negative results on all 3 conventional markers, most of whom had tumors size smaller than 3 cm; miR-16 was falsely positive in only 12 of 96 (12.5%) CLD patients. The addition of miR-16 to conventional serum markers improved sensitivity and specificity for HCC. Use of miR-16 for second-line testing in cases considered negative on the basis of conventional HCC markers should be explored in larger, prospective studies.